2000
DOI: 10.1093/aje/152.1.91
|View full text |Cite
|
Sign up to set email alerts
|

External Radiation Exposure and Mortality in a Cohort of Uranium Processing Workers

Abstract: In a study of 2,514 White male workers employed between 1942 and 1966 at a US uranium processing plant, mortality was compared with overall US mortality, and the relation between external ionizing radiation and cancer was evaluated. Through 1993, 1,013 deaths occurred. The mean cumulative dose was 47.8 mSv. The standardized mortality ratio (SMR) was 0.90 for all causes of death and 1.05 for all cancers. Many cancer sites had elevated SMRs. Among nonmalignant outcomes, the SMR for chronic nephritis was 1.88 (si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 15 publications
1
45
1
Order By: Relevance
“…Elevated mortality from lymphopoietic malignancies has already been described among workers with internal exposure to uranium (Guseva Canu et al 2008a). The most frequently reported causes were Hodgkin's disease (ICD-9:201) (Boice et al 2006;McGeoghegan and Binks 2000;Pinkerton et al 2004;Ritz 1999a, b), NHL (ICD-9: 202) (Atkinson et al 2004;Cardis et al 1995;Pinkerton et al 2004), and multiple myeloma (ICD-9: 203) (Baysson et al 2000;Checkoway et al 1988;Dupree-Ellis et al 2000;Loomis and Wolf 1996). However, as in our study, these results were often based on a small number of observed deaths and were rarely statistically signiWcant.…”
Section: Discussioncontrasting
confidence: 72%
“…Elevated mortality from lymphopoietic malignancies has already been described among workers with internal exposure to uranium (Guseva Canu et al 2008a). The most frequently reported causes were Hodgkin's disease (ICD-9:201) (Boice et al 2006;McGeoghegan and Binks 2000;Pinkerton et al 2004;Ritz 1999a, b), NHL (ICD-9: 202) (Atkinson et al 2004;Cardis et al 1995;Pinkerton et al 2004), and multiple myeloma (ICD-9: 203) (Baysson et al 2000;Checkoway et al 1988;Dupree-Ellis et al 2000;Loomis and Wolf 1996). However, as in our study, these results were often based on a small number of observed deaths and were rarely statistically signiWcant.…”
Section: Discussioncontrasting
confidence: 72%
“…DNA damage and chromosomal aberrations were found in the peripheral blood lymphocytes and leukocytes of those workers who were exposed to uranium compounds emerging from lowdose radiation [51][52][53][54][55][56]. Also, mortalities from kidney, bladder, and esophagus cancers were likely to increase, but chronic renal diseases were observed to be significantly higher [57][58][59].…”
mentioning
confidence: 99%
“…Port Hope, canada (Zablotska et al 2013), or in uranium processing nuclear industries such as Fernald, Ohio, USA (ritz 1999;Silver et al 2013), Mallinckrodt, Missouri, USA (Dupree-Ellis et al 2000) and ArEVA nc Pierrelatte, France (guseva canu et al 2010, 2011; guseva canu and garsi 2012). Millers and nuclear workers are exposed to a variety of occupational risk factors, namely uranium ore dust exposure, external gamma radiation and often radon and silica dust exposure.…”
mentioning
confidence: 99%